Effects of different Wx alleles on amylopectin molecular structure and enzymatic hydrolysis properties of rice starch. Issue 1 (1st January 2018) - Teng, Bin; Zhang, Chen; Zhang, Ying; Du, Shiyun; Xi, Min; Song, Fengshun; Ni, Jinlong; Luo, Zhixiang; Ni, Dahu
ABSTRACT: Allelic variation at the Wx locus plays a vital role in regulating apparent amylose content (AAC) as well as other important starch properties in rice grain. However, the extent of Wx allelic variation affecting amylopectin fine structure and enzymatic hydrolysis properties of rice starch remains unknown. In this paper, a series of rice single-segment substitution lines with five different Wx alleles ( wx, Wx t, Wx g1, Wx g2 and Wx g3 ) were used for comparative studies. The results showed that the five Wx alleles exhibited a wide variation in amylopectin molecular structure, hydrolysis and in vitro digestion properties of rice starch. Amylopectin chain length distribution as evaluated by fluorophore-assisted capillary electrophoresis was significantly different for the five Wx alleles, which might result in different functional properties. The hydrolysis degree of the five Wx genotype starches by α-amylase or amyloglucocidase was in the order wx > Wx t > Wx g1 >  Wx g3 >  Wx g2 . The rapidly digestible starch (RDS) content of the tested rice starches followed the order wx  =  Wx g3 >  Wx t  =  Wx g1 >  Wx g2 . The extent decrease of slowly digestible starch (SDS) content was wx  =  Wx t > Wx g1 >  Wx g2 >  Wx g3, while the trend in resistant starch (RS) content was Wx g2 >  Wx g3 >  Wx g1 >  Wx t > wx . Correlation analysis indicated that AAC was significantly positively correlated with RS but significantly negatively correlated with SDS and hydrolysis. The RDS showed a significant positive correlation with amylopectin short chains (DP 6–12) but no significant correlations with other structural properties. The present results could provide important information for the application of rice starches with different Wx genotypes.